2008
DOI: 10.4141/cjps07020
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of the invasive plant Coreopsis grandiflora at different altitudes in Laoshan Mountain, China

Abstract: . 2008. Genetic diversity of the invasive plant Coreopsis grandiflora at different altitudes in Laoshan Mountain, China. Can. J. Plant Sci. 88: 831Á837. In order to understand the relationship between genetic diversity and the invasiveness of exotic plants, genetic diversity was studied in the invasive plant Coreopsis grandiflora Hogg. at different altitudes in Laoshan Mountain, Northern China. Coreopsis grandiflora has produced a great deal of damage in Laoshan Mountain. Its genetic diversity was examined usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…However, there are few studies about alien plant invasion in Mount Tai and Mount Lao. Most studies just focused on certain alien plants which have caused damage to the environment, for example, Robinia pseudoacacia and Coreopsis grandiflora (Liang et al, 2008;Lv et al, 2013). In this study we conduct field investigation in two mountain regions (Mount Tai and Mount Lao), which have different climate features, to compare whether altitudinal richness patterns vary between native and alien species, to test whether alien species richness in different climate conditions present a consistent altitudinal pattern and to explore the invasion mechanisms of alien species in the understory of mountain forests to provide important guidance for controlling and managing the invasion of alien plants in mountain forests.…”
Section: Introductionmentioning
confidence: 97%
“…However, there are few studies about alien plant invasion in Mount Tai and Mount Lao. Most studies just focused on certain alien plants which have caused damage to the environment, for example, Robinia pseudoacacia and Coreopsis grandiflora (Liang et al, 2008;Lv et al, 2013). In this study we conduct field investigation in two mountain regions (Mount Tai and Mount Lao), which have different climate features, to compare whether altitudinal richness patterns vary between native and alien species, to test whether alien species richness in different climate conditions present a consistent altitudinal pattern and to explore the invasion mechanisms of alien species in the understory of mountain forests to provide important guidance for controlling and managing the invasion of alien plants in mountain forests.…”
Section: Introductionmentioning
confidence: 97%
“…Coreopsis America [114] Flower [115] Soil disturbance [116] Phenolics [117] Activity: antioxidant, antiinflammatory, antimicrobial, antimalarial, antileishmanial, and anti-Alzheimer [117] Flower: food additive…”
Section: Hogg Ex Sweetmentioning
confidence: 99%
“…Coreopsis America [114] Flower [115] (oils essential), phenolics [106,107,109] antimicrobial, antiprotozoal, hepatoprotective, neuroprotective, and gastroprotective [106,107] Asteraceae Chrysanthem um morifolium Ramat Chrysanthema Asia [3] Flower [3] Soil decontamination with Pb Pyrethroids (pyrethrins, deltamethrin), terpenes (sesquiterpene lactones), and phenolics (chrysanthemin) [3,110] Treatment: used in the detoxification of blood, regulation of pressure, calming nerves, hypertension, angina, digestive system, muscularskeletal system, respiratory system, arteriosclerosis, hypertension [3,111,112] Activity: antioxidant, antiinflammatory, anti-carcinogenic [111] Toxicity: the flowers present phytodermatitis [55] Flower: infusion, food supplement [3,111,113] Asteraceae…”
Section: Coreopsis Grandiflora Hogg Ex Sweetmentioning
confidence: 99%
“…In a study on the Yangtze River system, Jiang et al Studies on the genetic variation or diversity of non-native plants revealed a very low genetic diversity in most clonal invasive plants such as Alternanthera philoxeroides and Eichhornia crassipes (Mart.) Solms (e.g., Ye et al 2003, Ren et al 2005, while a relatively high genetic diversity has been found for a few species, such as Coreopsis grandiflora (Liang et al 2008) and Conyza sumatrensis (Ren et al 2010). Hao et al (2011) illustrated a higher probability of spreading and covering a broad range in self-compatible than in self-incompatible species of Asteraceae in China.…”
Section: Biological Featuresmentioning
confidence: 99%